Antimicrobial, antibiofilm and antioxidant activities of bioactive secondary metabolites of marine Scarus ghobban gut-associated Aspergillus niger: In-vitro and in-silico studies - Hagar Abdellatief; Amira E. Sehim; Amany M. Emam; Mahmoud Amer; Sawsan Dacrory; Amr H. Hashem (Scientific Reports)
Abstract Fungal extracts have garnered significant interest in recent years for their diverse applications in pharmaceutical field. This research focused on isolating fungi from the gut of Scarus ghobban for the first time and evaluate their biological activities Aspergillus niger was successfully isolated and identified using morphological and molecular techniques. Gas chromatography–mass spectrometry (GC-MS) analysis of the ethyl acetate extract (EA) of A. niger revealed eight compounds, with diisooctyl phthalate (54.32%) and 1,2-benzenedicarboxylic acid, bis (2-methoxyethyl) ester (26.32%) as the most abundant. High-performance liquid chromatography (HPLC) analysis identified catechol (15.41 µg/mL) and syringenic acid (13.25 µg/mL) as prominent phenolic compounds in the extract. The EA extract exhibited significant antibacterial activity toward pathogenic bacterial strains, with the highest inhibition zone (32 ± 0.1 mm) and minimum inhibitory concentration (MIC) of 7.8 µg/mL against Bacillus subtilis. Additionally, it showed antifungal activity against Candida tropicalis (MIC 7.8 µg/mL) and Candida albicans (MIC 31.25 µg/mL). The extract also demonstrated potential antibiofilm activity against Salmonella typhimurium, Staphylococcus aureus, Enterococcus faecalis, and Escherichia coli, with inhibition percentages exceeding 87%. Moreover, it exhibited potent antioxidant activity IC50 8.17 µg/mL. Transmission electron microscopy revealed severe structural damage in B. subtilis, emphasizing the extract’s antibacterial effectiveness and potential for therapeutic applications. Eventually, docking studies and computational calculations have been utilized to demonstrate the reactivity of the molecules. In conclusion, the ethyl acetate extract of A. niger from gut of S. ghobban demonstrates significant antibacterial, antibiofilm, and antioxidant activities, highlighting its potential as a valuable resource for developing effective antimicrobial agents and therapeutic applications.